2021
DOI: 10.21203/rs.3.rs-1019346/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction of a Convenient Screening Method for P-Hydroxybenzoate Hydroxylase To Enable Efficient Gallic Acid and Pyrogallol Biosynthesis

Abstract: BackgroundGallic acid (GA) and pyrogallol are phenolic hydroxyl compounds and have diverse biological activities. Microbial-based biosynthesis of GA and pyrogallol has been emerged as an ecofriendly method to replace the traditional chemical synthesis. In GA and pyrogallol biosynthetic pathways, the low hydroxylation activity of p-hydroxybenzoate hydroxylase (PobA) towards 3,4-dihydroxybenzoic acid (3,4-DHBA) limited the high-level biosynthesis of GA and pyrogallol.ResultsThis work reported a high active PobA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Overexpressing shikimate reductase from Juglans regia (walnut) from Ecoli causes a fivefold rise in gallate contents in tobacco plants, according to Chen, Chen, Yu, and Huo [3] on the biosynthesis of pyrogallol groups. In a recent study, we found that the Saccharothrix espanaensis bacteria coumarate 3-hydroxylase SAM5 could caffeate in order to produce 3, 4 , or 5-trihydroxycinnamate whenever produced in Ecoli.…”
Section: Lignin-engineering Pathwaysmentioning
confidence: 99%
“…Overexpressing shikimate reductase from Juglans regia (walnut) from Ecoli causes a fivefold rise in gallate contents in tobacco plants, according to Chen, Chen, Yu, and Huo [3] on the biosynthesis of pyrogallol groups. In a recent study, we found that the Saccharothrix espanaensis bacteria coumarate 3-hydroxylase SAM5 could caffeate in order to produce 3, 4 , or 5-trihydroxycinnamate whenever produced in Ecoli.…”
Section: Lignin-engineering Pathwaysmentioning
confidence: 99%